Knowledge about sexually transmitted infections, HIV/AIDS, sexual resilience and risky sexual behavior in adolescents - Castillo-Arcos, Lubia (2024)
Introduction. Approximately one million people acquire sexually transmitted infections (STI) due to the practice of risky sexual behaviors, identifying lack of knowledge and low resilience as triggers for such behavior. Objective. Analyze the relationship of Knowledge about, sexually transmitted infections, HIV/AIDS, sexual resilience with risky sexual behavior in adolescents. Material and methods. Cross-sectional correlational study in 250 high school adolescents from southern Mexico, through a self-administered survey that consisted of a sociodemographic card, knowledge questionnaire about STI, HIV/AIDS, sexual resilience scale and sexual behavior scale. Results. The female sex prevailed with 59.2%, with an age of 15.9 years (SD = 0.49). The adolescents obtained 63.6 points (SD = 17.9) in the knowledge questionnaire about STI, HIV/AIDS and 62.70 points (SD = 17.69) in sexual resilience, while in the scale of risky sexual behavior obtained 80.67 points (SD = 17.07). A significant and positive relationship was found between sexual resilience and knowledge about STI, HIV/AIDS (rs= 0.210, p < 0,05), a positive and significant relationship was observed between risky sexual behavior and sexual resilience (rs= 0,171, p < 0.05). Likewise, a positive and significant correlation was identified. significant difference between risky sexual behaviors and knowledge about STI, HIV/AIDS (rs = 0.152, p < 0.05). Conclusions. Nursing professionals must direct actions towards the prevention of risk behaviors by strengthening the dimensions that make up the protective factors, to provide adolescents with the cognitive tools and skills to detect situations of vulnerability.